If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 99 = -99 + -9x Reorder the terms: 99 + 3x = -99 + -9x Solving 99 + 3x = -99 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 99 + 3x + 9x = -99 + -9x + 9x Combine like terms: 3x + 9x = 12x 99 + 12x = -99 + -9x + 9x Combine like terms: -9x + 9x = 0 99 + 12x = -99 + 0 99 + 12x = -99 Add '-99' to each side of the equation. 99 + -99 + 12x = -99 + -99 Combine like terms: 99 + -99 = 0 0 + 12x = -99 + -99 12x = -99 + -99 Combine like terms: -99 + -99 = -198 12x = -198 Divide each side by '12'. x = -16.5 Simplifying x = -16.5
| (x-2)-x(x-2)=0 | | 0.3333(15x+975)=4000 | | 5-2p=15-3p | | (5x+3)+(5x-3)+90=180 | | -p*p= | | y^2-2y+1=16 | | 0.125(x+230)=200 | | -2(3x-5)= | | 2y+16=180 | | 2(2y+16)=7y-7 | | 188-5x=40x+18 | | (3z+5)+(2z-10)+90=180 | | 3n-5=-(6+5n) | | (4y+8)+(3y-9)+90=180 | | 2(x+1)-x(x+1)=0 | | b-1819=2300 | | 3(d+6)=12(d+3) | | -1.3+0.4= | | 12x+20=3x+209 | | 4x+10=2(3x-11) | | 7x+21=7 | | 6z+6=2(4z-16) | | 2x^2+9x-1= | | 12-9x=74-23x | | -5x+2=2 | | 24x+(-2)=2x+3 | | (2x+1)3-(x+4)5=5-(5x+1) | | g=3+h | | 75x-5x=8x+32 | | 667=29j | | 6+4=10 | | 4z+9=45 |